LANDASAN FILOSOFIS HUKUM PROGRESIF - Hyronimus Rhiti (Justitia et Pax, 2016)
AbstractSatjipto Rahardjo’s Progressive Law (Hukum Progresif) is intended to be an antithesis to the modern law, but the philosophical foundation of this law is not so clear. This article, based on literature research, try to find out the philosophical basis for this kind of law. With research methods and particular approaches, the possibility of philosophical foundation are exlplored. First, in the basic ideas of Progressive Law such as “law for human, sociology oriented law, liberation law, etc.” we can see the philosophical direction of this law. Second, based on certain philosophy, we can say that the metaphysical anthropology, realism, process philosophy and “postmodernism” are the roots of philosophy of Progressive Law.Keywords :progressive law, philosophical foundation,postmodernismIntisariHukum Progresif dari Satjipto Rahardjo dimaksudkan sebagai antitesis terhadap hukum modern. Meskipun demikian, belum jelas landasan filosofis hukum ini. Dengan metode penelitian dan pendekatan tertentu dicari kemungkinan landasan filosofis bagi hukum ini. Pertama, berdasarkan ide-ide dasar Hukum Progresif seperti “hukum untuk manusia”, “orientasi sosiologis” dan “pembebasan”, arah dari filosofis hukum ini dapat diketahui. Kedua, berdasarkan filsafat tertentu dapat dikatakan, bahwa antropologi metafisika, realisme, filsafat proses dan postmodernisme merupakan akar filsafat dari Hukum Progresif.Kata Kunci : hukum progresif, landasan filosofis, paska modernisme